Influence of different amount of Na2O additive on the structure, mechanical properties and degradability of bioactive wollastonite. Issue 1 (January 2016) - Li, H.C.; Wang, D.G.; Chen, C.Z.; Weng, F.; Shi, H.
Abstract: Wollastonite (CaSiO3 ) ceramics with various Na2 O contents (0, 5, 10, 15 and 20 mol%) were successfully prepared by sintering sol–gel derived precursors. The ceramics are composed of β-CaSiO3 . With increasing Na2 O content, Na2 Ca2 Si3 O9, Na4 Ca4 Si6 O18 and Na2 CaSi3 O8 are observed. The particle size distribution obeys the normal distribution. Na2 O decreases the total pore volume of wollastonite powder, and increases the apparent porosity of wollastonite ceramic block. Na2 O increases the bending strength of wollastonite, and the elastic moduli of all ceramics match that of cancellous bone of human body. The thermal expansion coefficients (TECs) of the ceramics are all close to that of titanium alloy (Ti6Al4V). The degradation rate is increased with increasing Na2 O content. All samples show the ability of apatite induction in simulated body fluid (SBF) solution.